2010
DOI: 10.1016/j.juro.2010.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Enucleation and Resection of Prostate in Patients With Benign Prostatic Hyperplasia by Plasma Kinetics

Abstract: Transurethral enucleation and resection of the prostate appears to be the modern alternative to transurethral resection of the prostate and open prostatectomy for bladder outlet obstruction due to benign prostatic hyperplasia. It may be done in glands up to 250 gm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 15 publications
4
130
2
2
Order By: Relevance
“…The TUERP procedure was performed using the Gyrus Plasmakinetic SuperPulse System (Gyrus Medical, Cardiff, UK) with PlasmaSect electrodes, operated with a cutting power of 160 W and a coagulating power of 80 W [10]. The TUERP technique has been described in detail elsewhere [6]. Briefly, this technique involved retrograde enucleation of the prostatic adenoma lobes following triradiate bladder neck incisions.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The TUERP procedure was performed using the Gyrus Plasmakinetic SuperPulse System (Gyrus Medical, Cardiff, UK) with PlasmaSect electrodes, operated with a cutting power of 160 W and a coagulating power of 80 W [10]. The TUERP technique has been described in detail elsewhere [6]. Briefly, this technique involved retrograde enucleation of the prostatic adenoma lobes following triradiate bladder neck incisions.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…A prospective randomized study comparing TUERP and TURP demonstrated the efficacy of TUERP, as shown by improvements in subjective and objective parameters [5][6][7][8][9]. Less is known, however, about the long-term (>5 years) efficacy, safety, and durability of TUERP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several studies have been conducted to find a new, safe, and efficient technology that combines the advantages of open and minimally invasive surgery [2,8]. Laser prostatectomy is a promising surgical technique [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of surgical methods are available, such as "orange peel" type [15], "fish scale" type [16], and transurethral dividing vaporesection [17]. Recently, more studies have verified the safety and efficiency of the enucleation technique to treat BPH since the report of Gilling et al [10,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation